Instrument for assessing coronary symptoms in women - Cándida Rosa Castañeda Valencia (Universidad Nacional de Colombia, 2015)
Objective: To design and validate an instrument for assessing the symptoms in women with coronary disease framed in the Theory of the Unpleasant Symptoms. Methodology: Methodological, psychometric study oriented by The symptoms, first concept of the Theory of Unpleasant Symptoms by Lenz et al. Theoretical critique of the construct chosen was performed proving usefulness in research and practice discipline. From the empirical, 260 evidences were weighted through methodological and empirical critique, applying the Integrative Review System articulated to the Empirical Conceptual Model by Fawcett Garity. Only 30 research pieces were obtained, used for the construction of the items. To the Lenz symptoms were added the reported psychosocial symptoms in women with coronary disease, generating a first design composed of 87 items. Results:The design was done by experts Content Validation with the Escobar and Cuervo Model 2008 (statistical analysis spss, 20) with Kendall Correlation Coefficient k = 0.682 (p ; 0.05) with good agreement between judges. Lawshe Model normalized by Tristán 2008 reported a Content Validity Ratio = 0.57 and Content Validity Index = 0.797, showing that items are units of essential analysis. Finally, Validation Facial made by means of the pilot test, conducted on 21 women who met the inclusion criteria, allowed the discrimination semiotics of items, obtaining an instrument consisting of 67 items.  Conclusions:This is a remnant of research that requires further validation to increase its psychometric capacity.